(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Virtual Reality (VR) has revolutionized teacher education by providing immersive, interactive environments that simulate real-world intercultural interactions, fostering empathy, cultural awareness, and communicative competence among pre-service English teachers. This article explores VR’s pedagogical potential in enhancing these skills, drawing on recent empirical studies (2023–2025) that demonstrate improved cultural intelligence and classroom management through VR simulations. Key findings indicate that VR’s core features—immersion, interaction, and imagination—outperform traditional methods in building intercultural competence, with effect sizes up to 0.8 in randomized trials. However, challenges like accessibility and technical barriers persist, particularly in resource-limited settings. Through a synthesis of mixed-methods research, this study proposes a framework for integrating VR into English teacher training curricula, emphasizing student-centered, experiential learning. Implications include enhanced global readiness for pre-service teachers, with recommendations for scalable VR adoption in diverse educational contexts.